2009
DOI: 10.1007/s10661-009-1069-4
|View full text |Cite
|
Sign up to set email alerts
|

The study of heavy metal pollution and accumulation in water, sediment, and fish tissue in Kızılırmak River Basin in Turkey

Abstract: The accumulation of heavy metals such as Pb, Hg, Co, Cr, Cu, Zn, and Br were determined in water, sediment, muscle, and gill of three fish species (Leuciscus cephalus, Capoeta tinca, Capoeta capoeta) which were collected in Kizilirmak River Basin (Delice River). The metal concentration showed a general trend of Br>Zn>Pb>Cr>Cu>Hg>Co in water and Cr>Zn>Pb>Cu>Co>Hg>Br in sediment samples while Zn>Cu>Pb>Br>Cr>Hg>Co were in muscle and Zn>Pb>Cu>Cr>Br>Hg>Co were in the gill tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…The found range of Cd is comparable to those found by Tuzen (2003), Akbulut and Akbulut (2010) and Ergul et al (2008) for samples from Yeşilırmak, Kızılırmak and Black Sea coast, respectively. For Pb, Cu, Zn and Mn, the obtained results are considered to be lower compared to the concentrations found by the Black Sea Coast study (Ergul et al 2008) mentioned in Table 6.…”
Section: Pseudototalsupporting
confidence: 85%
See 1 more Smart Citation
“…The found range of Cd is comparable to those found by Tuzen (2003), Akbulut and Akbulut (2010) and Ergul et al (2008) for samples from Yeşilırmak, Kızılırmak and Black Sea coast, respectively. For Pb, Cu, Zn and Mn, the obtained results are considered to be lower compared to the concentrations found by the Black Sea Coast study (Ergul et al 2008) mentioned in Table 6.…”
Section: Pseudototalsupporting
confidence: 85%
“…The mean amount of Pb in this study (41.31 μg/g) was almost within the amount of that reported by Ergul et al (2008) for sediments collected from Black Sea Coast. However, Tuzen (2003) and Akbulut and Akbulut (2010) reported lower values of Pb (29.60 and 30.56 μg/g, respectively). The range of Cd obtained in this study is considered higher compared to the result reported by Ergul et al (2008).…”
Section: Pseudototalmentioning
confidence: 83%
“…The decrease of heavy metals in warm seasons and winter in maybe cause by heavy rain, snow and melting snow. Similar results are also found in Hazar Lake (KaradedeAkın, 2009), Karataş Lake (Başyiğit and TekinÖzan, 2013), Kızılırmak River Basin (Akbulut and Akbulut, 2010).…”
Section: Resultssupporting
confidence: 79%
“…Among the analyzed metals, the highest and lowest metals were Fe and Cd. Similar results were reported in Beyler Reservoir (Fındık, 2013), Hazar Lake (Karadede-Akın, 2009), Karataş Lake (Başyiğit and Tekin-Özan, 2013), Kızılırmak River (Akbulut and Akbulut, 2010), Beyşehir Lake (Tekin-Özan, 2008). Ghaffar et al (2008), reported that Fe facilities the precipitation of other metals and found at low levels when precipitation occurs.…”
Section: Resultssupporting
confidence: 70%
“…The samples were taken from four different stations in February, May and August 2008. The metal concentrations in the sediment samples were sequenced as: Cr > Zn > Pb > Cu > Co > Hg > Br [36]. According to the researchers, if these water bodies are to be used as drinking water and agricultural water sources, they must be biomonitored in order to keep tabs on their heavy metal concentrations.…”
Section: Rivers and Streamsmentioning
confidence: 99%